Method for producing glass resin laminate

By using rollers with elastic surface layer during the lamination process of glass film and resin film and controlling the elasticity range of the adhesive layer, the bubble defect problem caused by foreign matter adhesion is solved, and under the conditions of thin adhesive layer, the bubble defects are realized bubble defect suppression effect.

CN113613868BActive Publication Date: 2025-02-25NITTO DENKO CORP
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202080023694.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-11
Publication Date
2025-02-25
Estimated Expiration
2040-03-11

AI Technical Summary

Technical Problem

During the lamination process of the glass film and the resin film, when foreign matter adheres to the roller surface, the resin film deforms and bubble defects occur, which is more significant, especially when the adhesive layer is thin.

Method used

The occurrence of bubble defects is suppressed by sandwiching the glass film and the resin film between the rollers having the elastic surface layer and ensuring that the elasticity of the adhesive layer is within the range of 3×10-3≤P1/P2≤1.0.

Benefits of technology

The occurrence of bubble defects is effectively suppressed, and even when the adhesive layer is thin, the number of bubble defects can be significantly reduced and the quality of the product can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113613868B_ABST
    Figure CN113613868B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a glass resin laminate, which comprises the steps of sandwiching a glass film and a resin film between a first roller for pressing the resin film and a second roller arranged opposite to the first roller and pressing the glass film, and bonding the glass film and the resin film together with an adhesive layer, wherein when the elastic modulus of the surface layer of the first roller is P1 and the elastic modulus of the resin film is P2, the ratio P1 / P2 of the elastic modulus P1 to the elastic modulus P2 satisfies 3×10 -3 ≤P1 / P2≤1.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a glass resin laminate. Background Art

[0002] In recent years, liquid crystal units with touch sensor functions installed on the screen have been widely used in various fields from mobile phones to information displays.

[0003] As an example, a display panel can be cited in which a film or glass having a sensor function is laminated on a polarizing plate, and a tempered glass called a "front plate" is arranged on the outermost layer via an adhesive layer for filling the step difference (step) on the sensor surface. In addition, a liquid crystal panel called an "in-cell" has recently appeared in which a touch sensor is embedded in the glass substrate of the liquid crystal unit from the perspective of thinning and weight reduction.

[0004] On the other hand, the thinning of tempered glass is also in progress, but if the tempered glass is less than 300μm, self-damage will occur due to the compressive stress of the glass, so the thinning is limited. In this case, although the use of resin to increase the hardness of the front plate has been studied, it is actually impossible to obtain sufficient hardness.

[0005] Therefore, thin glass films have attracted attention as front plates of liquid crystal cells. The glass films can be laminated with resin films including polarizing plates via adhesive layers, for example. The adhesive layers tend to be thinner due to the need for thinner products, etc.

[0006] [Reference document]

[0007] [Patent document]

[0008] [Patent Document 1] International Publication No. 2013 / 175767 Summary of the invention

[0009] [Technical issues to be solved]

[0010] However, when laminating the glass film and the resin film, for example, the glass film and the resin film are sandwiched between two rollers arranged adjacent to each other. At this time, if foreign matter adheres to the surface of the roller on the side in contact with the resin film, the glass film with higher rigidity will not be deformed, but the resin film with lower rigidity will be deformed.

[0011] For this reason, the side of the resin film that contacts the glass film may have a concave-convex shape corresponding to the shape of the foreign matter, causing air to enter the concave part, and then generating air bubble defects. In particular, when the thickness of the adhesive layer is thin, the occurrence of air bubble defects is more significant. As a product, the fewer the number of air bubble defects, the better.

[0012] The present invention is proposed in view of the above-mentioned problems, and its object is to provide a method for manufacturing a glass-resin laminate that can suppress the occurrence of bubble defects compared with the conventional method when a glass film and a resin film are laminated via an adhesive layer even when the adhesive layer is thin.

[0013] [Technical solution]

[0014] The present invention relates to a method for manufacturing a glass resin laminate, which comprises the steps of sandwiching a glass film and a resin film between a first roller for pressing the resin film and a second roller arranged opposite to the first roller and pressing the glass film, and bonding the glass film and the resin film together by an adhesive layer. When the elastic modulus of the surface layer of the first roller is set to P1 and the elastic modulus of the resin film is set to P2, the ratio P1 / P2 of the elastic modulus P1 to the elastic modulus P2 satisfies 3×10 -3 ≤P1 / P2≤1.0.

[0015] [Beneficial Effects]

[0016] According to the disclosed technology, it is possible to provide a method for manufacturing a glass-resin laminate that can suppress the occurrence of bubble defects compared to conventional methods when a glass film and a resin film are laminated via an adhesive layer, even when the adhesive layer is thin. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] [ Figure 1 ]Example cross-sectional view of a glass resin laminate.

[0018] [ Figure 2 ] Illustration of the steps of laminating a glass film on a resin film.

[0019] [ Figure 3 ] Illustration of the conventional problems when laminating a glass film on a resin film.

[0020] [ Figure 4 ] Illustration of a method for suppressing the occurrence of bubble defects.

[0021] [ Figure 5 ] Figure 4 Magnified view of part A. DETAILED DESCRIPTION

[0022] Hereinafter, the form (mode) for implementing the invention will be described with reference to the drawings. In each figure, the same components are given the same reference numerals and overlapping descriptions may be omitted.

[0023] (Glass-resin laminate)

[0024] First, the glass resin laminate to be produced will be described. Figure 1is an exemplary cross-sectional view of a glass resin laminate, Figure 1 (a) shows the glass film and the resin film before lamination, Figure 1 (b) shows the glass film and the resin film after lamination (ie, a glass-resin laminate).

[0025] The glass-resin laminate 1 includes a glass film 10 and a resin film 20 . The glass film 10 is bonded to the resin film 20 via an adhesive layer 21 of the resin film 20 .

[0026] As for the glass film 10, there is no particular limitation, and an appropriate glass film can be used according to the purpose of use. When the glass film 10 is classified according to the composition (ingredients), for example, soda lime glass, boric acid glass, aluminosilicate glass, quartz glass, etc. can be listed. In addition, when classified according to the alkali component, alkali-free glass and low-alkali glass can be listed. The content of the alkali metal component (for example, Na2O, K2O, Li2O) of the above-mentioned glass is preferably less than 15% by weight, and preferably less than 10% by weight.

[0027] The thickness of the glass film 10 is preferably 50 μm to 150 μm, more preferably 60 μm to 140 μm, more preferably 70 μm to 130 μm, and particularly preferably 80 μm to 120 μm. Within this range, processing based on a roll-to-roll process with good flexibility can be performed, and a glass resin laminate 1 with a glass film that is not easily broken and excellent in productivity can be obtained.

[0028] The light transmittance of the glass film 10 at a wavelength of 550 nm is preferably 85% or more. The refractive index of the glass film 10 at a wavelength of 550 nm is preferably 1.4 to 1.65.

[0029] The density of the glass film 10 is preferably 2.3 g / cm 3 ~3.0g / cm 3 , preferably 2.3g / cm 3 ~2.7g / cm 3 As long as the glass film is within this range, a lightweight glass resin laminate 1 that contributes to image display can be provided.

[0030] There is no particular limitation on the forming method of the glass film 10, and an appropriate forming method can be adopted according to the purpose of use. Generally, the glass film 10 can be produced by the following method, that is, a mixture containing main raw materials such as silicon dioxide and aluminum oxide, a defoaming agent such as sodium sulfate and antimony oxide, and a reducing agent such as carbon is melted at a temperature of about 1400°C to 1600°C, and formed into a thin plate, and then cooled, thereby producing the glass film 10. As the forming method of the glass film 10, for example, a groove down-drawing method, a melting method, a float method, etc. are listed. For the glass film formed into a plate by these methods, in order to thin it or improve the smoothness, it can also be chemically polished using a solvent such as fluoric acid as needed.

[0031] The resin film 20 includes an adhesive layer 21, a polarizing plate 22, an adhesive layer 28, and a release film 29 in this order. However, the resin film 20 may also include other layers. For example, the resin film 20 may include a phase difference layer between the polarizing plate 22 and the adhesive layer 28, but is not limited thereto.

[0032] It should be noted that the adhesive layer 21 may be provided on the glass film 10. In this case, the resin film 20 includes the polarizing plate 22, the adhesive layer 28, and the release film 29 in this order, and may further include other layers as necessary.

[0033] The elastic modulus of the resin film 20 is preferably 0.1 GPa to 8.0 GPa, more preferably 0.2 GPa to 7.0 GPa, and more preferably 0.3 GPa to 5.0 GPa. In the present specification, the elastic modulus can be measured by a precision universal testing machine (Autograph) under the following conditions.

[0034] [Elastic modulus measurement method]

[0035] Measurement temperature: 23°C

[0036] Sample size: 2cm wide, 15cm long

[0037] Distance between chucks: 10cm

[0038] Stretching speed: 10mm / min.

[0039] It should be noted that in this specification, the adhesive layer refers to a layer that has adhesiveness at room temperature and can be bonded to an adherend by a lighter pressure. Therefore, even when the adherend bonded to the adhesive layer is peeled off, the adhesive layer can also maintain a practical adhesive force. On the other hand, the adhesive layer refers to a layer that can combine substances by being present between substances. Therefore, when the adherend bonded to the adhesive layer is peeled off, the adhesive layer does not have a practical adhesive force.

[0040] The polarizing plate 22 is arranged on the side of the adhesive layer 21 opposite to the side bonded to the glass film 10. The polarizing plate 22 includes a polarizer 221, a first protective film 222, and a second protective film 223. The first protective film 222 is arranged on the adhesive layer 21 side of the polarizer 221, and the second protective film 223 is arranged on the adhesive layer 28 side of the polarizer 221.

[0041] The release film 29 is disposed on the side of the second protective film 223 opposite to the polarizer 221 via the adhesive layer 28 .

[0042] Hereinafter, each component of the resin film 20 will be described in more detail.

[0043] [Adhesive layer]

[0044] As for the adhesive layer 21, there is no particular limitation on it, and an appropriate adhesive can be used according to the purpose of use. As adhesives, for example, polyester adhesives, polyurethane adhesives, polyvinyl alcohol adhesives, and epoxy adhesives can be listed. Among them, epoxy adhesives that can obtain particularly good adhesion (close contact) are preferred.

[0045] In the case where the adhesive layer 21 is a thermosetting adhesive, it can exhibit peeling resistance by being hardened (cured) by heating. In addition, in the case where the adhesive layer 21 is a light-curing adhesive such as an ultraviolet curing adhesive, it can exhibit peeling resistance by being hardened by irradiating light such as ultraviolet rays. In addition, in the case where the adhesive layer 21 is a moisture-curable adhesive, it can react with moisture in the air to harden, so it can also be hardened by being left alone, thereby exhibiting peeling resistance.

[0046] For example, a commercially available adhesive may be used as the adhesive layer 21 , or an adhesive solution (or dispersion) may be prepared by dissolving or dispersing various curable resins in a solvent.

[0047] The thickness of the adhesive layer 21 is preferably 8 μm or less, preferably 0.1 μm to 8 μm, more preferably 0.1 μm to 5 μm, and particularly preferably 0.1 μm to 2 μm. Within such a range, a glass resin laminate 1 having good flexibility and excellent puncture resistance can be obtained. In addition, the thinner the adhesive layer 21, the thinner the glass resin laminate 1, so the requirement for thinning the product can be met.

[0048] The elastic modulus of the adhesive layer 21 is preferably 0.5 GPa to 15 GPa, more preferably 0.8 GPa to 10 GPa, and more preferably 1 GPa to 5 GPa. Within such a range, a glass resin laminate 1 having excellent flexibility and excellent puncture resistance can be obtained.

[0049] It should be noted that Figure 1 The adhesive layer 21 in the state (a) (before lamination) is not hardened. Figure 1 As shown in (b), after the glass film 10 is laminated on the resin film 20, the adhesive layer 21 is cured, thereby obtaining a glass resin laminate 1 in which the glass film 10 and the resin film 20 are bonded together. The method for manufacturing the glass resin laminate 1 in which the glass film 10 and the resin film 20 are bonded together by the adhesive layer 21 will be described in detail later.

[0050] [Polarizing plate]

[0051] The thickness of the polarizing plate 22 is preferably 5 μm to 300 μm, more preferably 10 μm to 250 μm, more preferably 25 μm to 200 μm, and particularly preferably 25 μm to 100 μm.

[0052] The elastic modulus of the polarizing plate 22 is preferably 1 GPa or more, more preferably 1 GPa to 10 GPa, more preferably 2 GPa to 7 GPa, and particularly preferably 2 GPa to 5 GPa. Within such a range, a glass resin laminate 1 having excellent puncture resistance can be obtained.

[0053] As for the shape of the polarizing plate 22, there is no particular limitation on it, and an appropriate shape can be adopted according to the purpose of use. As an example, a rectangular shape with long sides and short sides can be listed. In the case where the polarizing plate 22 is rectangular, it is preferred that the absorption axis direction of the polarizer 221 of the polarizing plate 22 is roughly parallel to the long side or short side of the polarizing plate 22. It should be noted that in this specification, the concept of "roughly parallel" refers to not only the case of strict parallelism, but also the case where the angle between the two lines is ±10° (preferably ±5°).

[0054] [Polarizer]

[0055] There is no particular limitation on the thickness of the polarizer 221, and an appropriate thickness can be used according to the purpose of use. The thickness of the polarizer 221 is usually about 1 μm to 80 μm. As the polarizer 221, a thinner polarizer can be used. In this case, the thickness of the polarizer 221 is preferably 20 μm or less, preferably 15 μm or less, more preferably 10 μm or less, and particularly preferably 6 μm or less.

[0056] The polarizer 221 preferably has absorption dichroism at any wavelength within the wavelength range of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 40.0% or more, preferably 41.0% or more, more preferably 42.0% or more, and particularly preferably 43.0% or more. The polarization degree of the polarizer 221 is preferably 99.8% or more, preferably 99.9% or more, and more preferably 99.95% or more.

[0057] The polarizer 221 is preferably an iodine-based polarizer. Specifically, the polarizer may be composed of a polyvinyl alcohol-based resin (hereinafter referred to as "PVA-based resin") film containing iodine.

[0058] The PVA-based resin forming the PVA-based resin film is not particularly limited, and an appropriate resin can be adopted depending on the intended use. Examples of the resin include polyvinyl alcohol and ethylene-vinyl alcohol copolymer.

[0059] Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer can be obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA-based resins is generally 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be obtained based on JIS K6726-1994. By using PVA-based resins with such a saponification degree, a polarizer with better durability can be obtained. However, if the saponification degree is too high, gelation may also occur.

[0060] The average degree of polymerization of the PVA resin is not particularly limited and can be appropriately selected according to the intended use. The average degree of polymerization of the PVA resin is, for example, 1000 to 10000, preferably 1200 to 5000, and more preferably 1500 to 4500. It should be noted that the average degree of polymerization can be obtained based on JIS K 6726-1994.

[0061] As a method for manufacturing the polarizer 221, for example, there can be cited a method (I) of stretching and dyeing a PVA-based resin film monomer, a method (II) of stretching and dyeing a laminate (i) having a resin substrate and a polyvinyl alcohol-based resin layer, etc. Method (I) is a conventional method well known in the industry, so its detailed description is omitted.

[0062] The method (II) preferably includes extending and dyeing a laminate (i) having a resin substrate and a polyvinyl alcohol resin layer formed on one side of the resin substrate, thereby preparing a polarizer on the resin substrate. The laminate (i) can be formed by applying a coating liquid containing a polyvinyl alcohol resin on a resin substrate and drying it. In addition, the laminate (i) can also be formed by transcribing the polyvinyl alcohol resin layer on a resin substrate. The details of the manufacturing method (II) are described in, for example, Japanese Patent Publication No. 2012-73580, which is cited in this specification as a reference.

[0063] [1st and 2nd protective films]

[0064] As the first protective film 222 and the second protective film 223, there is no particular limitation, and appropriate resin films can be used according to the purpose of use. As the forming materials of the first protective film 222 and the second protective film 223, for example, polyester resins such as polyethylene terephthalate (PET), cellulose resins such as triacetyl cellulose (TAC), cycloolefin resins such as norbornene resins, olefin resins such as polyethylene (Polyethylene) and polypropylene (Polypropylene), (meth) acrylic resins, etc. can be listed. Among these, polyethylene terephthalate (PET) is preferred. It should be noted that "(meth) acrylic resin" refers to acrylic resin and / or methacrylic resin.

[0065] As the (meth)acrylic resin, for example, a (meth)acrylic resin having a glutarimide structure can be used. The (meth)acrylic resin having a glutarimide structure (hereinafter also referred to as glutarimide resin) is described in, for example, Japanese Patent Application Laid-Open Nos. 2006-309033, 2006-317560, 2006-328329, 2006-328334, 2006-337491, 2006-337492, 2006-337493, 2006-337569, 2007-009182, 2009-161744, and 2010-284840, the contents of which are incorporated herein by reference.

[0066] The first protective film 222 and the second protective film 223 may be laminated with the polarizer 221 via an appropriate adhesive layer. The resin substrate used in the production of the polarizer 221 may be peeled off before or after the first protective film 222 and the second protective film 223 are laminated with the polarizer 221.

[0067] The thickness of the first protective film 222 and the second protective film 223 is preferably 4 μm to 250 μm, more preferably 5 μm to 150 μm, more preferably 10 μm to 100 μm, and particularly preferably 10 μm to 50 μm.

[0068] The elastic modulus of the first protective film 222 and the second protective film 223 is 1 GPa or more, preferably 1 GPa to 10 GPa, more preferably 1.8 GPa to 7 GPa, and more preferably 2 GPa to 5 GPa. Within such a range, a glass resin laminate 1 having excellent puncture resistance can be obtained.

[0069] [Adhesive layer]

[0070] The adhesive layer 28 can be formed by any appropriate adhesive. As the adhesive, for example, an adhesive using acrylic polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyethers, fluororubbers and the like as base polymers can be used. Preferably, an acrylic adhesive is used. The reason is that the acrylic adhesive has excellent optical transparency, shows appropriate wettability, cohesion, and adhesive bonding properties, and has excellent weather resistance, heat resistance, etc. Acrylic adhesives made of acrylic polymers with a carbon number of 4 to 12 are particularly preferred.

[0071] The thickness of the adhesive layer 28 is preferably 1 μm to 100 μm, more preferably 3 μm to 80 μm, and more preferably 3 μm to 50 μm. Within this range, when the glass resin laminate 1 is attached to an optical element such as a liquid crystal cell to produce an optical laminate, an optical laminate having excellent flexibility and good puncture resistance can be obtained.

[0072] [Release film]

[0073] The release film 29 can be formed of a resin such as polyethylene terephthalate (PET), polyethylene (PE), or polypropylene (PP). The thickness of the release film 29 is preferably 5 μm to 125 μm, preferably 20 μm to 75 μm, and more preferably 30 μm to 50 μm. The release film 29 is peeled off from the interface with the adhesive layer 28 before the glass resin laminate 1 is attached to an optical element such as a liquid crystal unit.

[0074] (Method for producing glass resin laminate)

[0075] Next, with regard to the manufacturing method of the glass resin laminate, the manufacturing method is described by focusing on the steps of sandwiching the glass film 10 and the resin film 20 between a roller pressing the resin film 20 and a roller pressing the glass film 10 and bonding the glass film 10 and the resin film 20 together by the adhesive layer 21.

[0076] Figure 2 It is an explanatory diagram of the step of laminating a glass film on a resin film. Figure 2In the embodiment, the resin film 20 is suspended on rollers 110, 120, and 130 and is transported in the direction of the arrow. The resin film 20 can be transported, for example, by a roll-to-roll method. A roller 140 is arranged at a position opposite to the roller 110 in the vertical direction.

[0077] It should be noted that Figure 2 Although three rollers for conveying the resin film 20 are shown in the figure, this is only an example, and the number of rollers can be appropriately determined as needed.

[0078] The glass film 10 is conveyed in the arrow direction and is laminated on the resin film 20 between the roller 110 and the roller 140 . At this time, the roller 140 presses the glass film 10 , and the roller 110 presses the resin film 20 .

[0079] Thus, the glass film 10 can be laminated on the resin film 20. At this time, the adhesive layer 21 is not cured. The adhesive layer 21 is cured in a curing step (not shown) arranged downstream of the conveying direction (arrow direction) of the rollers 110 and 140, thereby forming a glass resin laminate 1. It should be noted that the thickness of the adhesive layer 21 does not change substantially before and after curing.

[0080] Here, problems that may occur when laminating the glass film 10 on the resin film 20 in the case of using the conventional method will be described. Figure 3 This is a diagram for explaining a conventional problem when laminating a glass film on a resin film.

[0081] Figure 3 In, replace Figure 2 The roller 110 shown is a roller 110X. The roller 110X is made of iron. That is, a portion of the roller 110X corresponding to the surface layer of the roller 110 is made of iron.

[0082] like Figure 3 As shown in FIG. 1 , foreign matter F may be attached to the roller 110X. In this case, when the glass film 10 is laminated on the resin film 20, the roller 110X side of the resin film 20 is in contact with the foreign matter F. However, at this time, the iron roller 110X and the glass film 10, which are relatively rigid, are basically not deformed, and the resin film 20, which is relatively low in rigidity, is mainly deformed. For this reason, a concave-convex shape corresponding to the shape of the foreign matter F appears on the side of the resin film 20 in contact with the glass film 10, causing air to enter the concave portion, thereby generating a bubble defect B.

[0083] The bubble defect B has a size that can be observed by human eyes. Therefore, when the glass resin laminate 1 is applied to a product such as a display device, only a certain number (quantity) of such bubble defects are allowed to exist, preferably zero as much as possible. Therefore, in order to solve such a problem that has existed before, a countermeasure for suppressing the occurrence of bubble defects B is proposed in this embodiment. Figure 4 and Figure 5 Explain it.

[0084] Figure 4 This is a diagram for explaining a method for suppressing the occurrence of bubble defects, and shows an enlarged Figure 2 The vicinity of the rollers 110 and 140. Figure 3 As described above, iron rollers are often used in the past. In this embodiment, the surface layer of roller 110 is formed of a material having a lower elastic modulus than iron. It should be noted that the surface layer refers to a region extending from the surface of roller 110 to about 1 mm inward in the center direction.

[0085] The material having a lower elastic modulus than iron is not particularly limited, and examples thereof include resins such as polyethylene terephthalate (PET), polyethylene (PE), and polypropylene (PP), and rubbers such as silicone rubber, polyurethane rubber, and nitrile rubber. Among these, silicone rubber having excellent flexibility is particularly preferred.

[0086] Figure 5 yes Figure 4 Magnified view of part A. Figure 5 In the process, the presence of the foreign matter F causes the surface layers of the resin film 20 and the roller 110 to be deformed.

[0087] Here, the length of the foreign matter F before compression in the direction perpendicular to the surface of the resin film 20 is t, and considering the compression when the glass film 10 is laminated on the resin film 20, the length of the foreign matter F after compression can be Δl=√t. This is based on the knowledge obtained by the inventors of the present invention.

[0088] In addition, of the length Δl of the compressed foreign matter F, the length on the resin film 20 side is Δlp, and the length on the roller 110 side is Δlr. At this time, if the elastic modulus of the resin film 20 is set to Ep, and the elastic modulus of the surface layer of the roller 110 is set to Er, then based on the relationship between the strain and elastic modulus on both sides of the foreign matter F, the following formula (1) can be derived.

[0089] [Formula 1]

[0090]

[0091] Furthermore, from the above description, it can be seen that the relationship among Δlp, Δlr, Δl, and √t is expressed by the following formula (2).

[0092] [Formula 2]

[0093]

[0094] Next, we will use formula (1) and formula (2) to discuss specific numerical examples. Here, the length t of the target foreign matter F before compression is about 20 to 100 μm. The reason is that if there is a foreign matter F of such a size, it is easy to produce a bubble defect B that can be observed by the human eye. Here, as an example, t = 100 μm.

[0095] Here, assuming that polyethylene terephthalate (PET) is used as the material of the surface layer of the roller 110, its elastic modulus is about 5 GPa. The elastic modulus of the resin film 20 is also about 5 GPa, so after calculating Δlp according to formula (1) and formula (2), it can be known that Δlp = 5 μm. That is, the amount of foreign matter F entering the resin film 20 is about 5 μm. At this time, the uncured adhesive layer 21 is relatively soft, so if the thickness of the adhesive layer 21 is more than 5 μm, the adhesive layer 21 will absorb Δlp. Based on this, Figure 4 As shown in FIG. 1 , the side of the resin film 20 that contacts the glass film 10 will not be deformed. Figure 3 The bubble defect B is shown.

[0096] In addition, if silicone rubber is used as the material of the surface layer of the roller 110, its elastic modulus is about 1.5 MPa. The elastic modulus of the resin film 20 is about 5 GPa, so after calculating Δlp according to formula (1) and formula (2), it can be known that Δlp = 3.0 × 10 -3 That is, the amount of foreign matter F entering the resin film 20 is 3.0×10 -3 At this time, the resin film 20 is basically not deformed, so even if the thickness of the adhesive layer 21 is extremely thin, the side of the resin film 20 that contacts the glass film 10 will not deform. Figure 3 The bubble defect B is shown.

[0097] That is, when the glass film 10 is laminated on the resin film 20 having the adhesive layer 21 with a thickness of 5 μm or less and an elastic modulus of about 5 GPa, the surface layer of the roller 110 is preferably formed of a material with a low elastic modulus such as polyethylene terephthalate (PET) or silicone rubber. Accordingly, even when foreign matter F is attached to the surface of the roller 110, deformation of the resin film 20 can be suppressed, and the occurrence of bubble defects B can be suppressed.

[0098] Thus, if the elastic modulus of the surface layer of the roller 110 is low, the deformation of the resin film 20 caused by the foreign matter F is small, thereby suppressing the occurrence of bubble defects B. In addition, if the deformation of the resin film 20 caused by the foreign matter F is small, the adhesive layer 21 is unlikely to contribute to the relaxation of the deformation, so that a thinner adhesive layer 21 can be used.

[0099] Further summarizing the above content, it can be seen that in the manufacturing step of the glass resin laminate, when the elastic modulus of the surface layer of the roller 110 is P1 and the elastic modulus of the resin film 20 is P2, as long as the ratio of the elastic modulus P1 to the elastic modulus P2 satisfies 3×10 -3 The material of the surface layer of the roller 110 may be selected in such a manner that ≤P1 / P2≤1.0. It should be noted that the portion other than the surface layer of the roller 110 may also be formed of the same material as the surface layer.

[0100] As for the above requirements (conditions), the thinner the adhesive layer that bonds the glass film and the resin film together, the better the effect. For example, when the thickness of the adhesive layer is 0.1 μm or more and 5 μm or less, the effect is particularly significant. In other words, when an adhesive layer with a thickness greater than 10 μm is used, the occurrence of bubble defects B can sometimes be suppressed even if the above conditions are not met. However, if the adhesive layer is thicker, problems such as reduced transportability of the resin film and prolonged curing time of the adhesive layer will occur, so the adhesive layer should not be more than 10 μm.

[0101] It should be noted that the above discussion does not mention the roller 140, but as far as the roller 140 is concerned, since the glass film 10 with high rigidity basically does not deform, it can be considered that the material of the surface layer of the roller 140 will not affect the above discussion. Therefore, the material of the surface layer of the roller 140 can be iron, resin, rubber, or other materials.

[0102] Hereinafter, lamination of the resin film and the glass film will be described in more detail by giving examples and comparative examples, but the present invention is not limited to these examples.

[0103] [Example 1]

[0104] In Example 1, a resin film having an elastic modulus of 5 GPa and a 2 μm thick adhesive layer was prepared, and a glass film was laminated on the resin film between rollers facing each other. Thereafter, the adhesive layer was cured to produce a glass resin laminate A. The surface layer of the roller in contact with the resin film was made of polyethylene terephthalate (PET) having an elastic modulus of 5 GPa.

[0105] [Example 2]

[0106] In Example 2, a glass resin laminate B was produced in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 5 μm.

[0107] [Example 3]

[0108] In Example 3, a glass resin laminate C was produced in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 10 μm.

[0109] [Comparative Example 1]

[0110] In Comparative Example 1, a resin film having an elastic modulus of 5 GPa and a 2 μm thick adhesive layer was prepared, and a glass film was laminated on the resin film between rollers facing each other. Thereafter, the adhesive layer was cured to produce a glass resin laminate D. Iron having an elastic modulus of 73 GPa was used as the surface layer of the roller in contact with the resin film.

[0111] [Comparative Example 2]

[0112] In Comparative Example 2, a glass resin laminate E was produced in the same manner as in Comparative Example 1 except that the thickness of the adhesive layer was changed to 5 μm.

[0113] [Comparative Example 3]

[0114] In Comparative Example 3, a glass resin laminate F was produced in the same manner as in Comparative Example 1 except that the thickness of the adhesive layer was changed to 10 μm.

[0115] [Evaluation (assessment)]

[0116] The number of bubble defects in the glass resin laminates A to F prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was visually inspected. The results are shown in Tables 1 and 2. It should be noted that when determining, if the number of bubble defects [ / m 2 ] is 50 or less, it is 0 (qualified), if it is more than 50, it is × (unqualified).

[0117] [Table 1]

[0118]

[0119] [Table 2]

[0120]

[0121] As shown in Table 1, when the surface layer of the roller in contact with the resin film is formed of polyethylene terephthalate (PET), the number of bubble defects is within the allowable range regardless of whether the thickness of the adhesive layer is 2 μm, 5 μm, or 10 μm. In particular, when the thickness of the adhesive layer is 5 μm or more, the number of bubble defects is 0, which is a very good result.

[0122] It should be noted that, based on the above research results, it can be predicted that if the surface layer of the roller in contact with the resin film is formed of silicone rubber, the number of bubble defects can be approximately zero even if the thickness of the adhesive layer is 2 μm or less.

[0123] On the other hand, as shown in Table 2, when iron is used for the surface layer of the roller in contact with the resin film, the number of bubble defects is 0 when the thickness of the adhesive layer is 10 μm, but the number of bubble defects exceeds the allowable range when the thickness of the adhesive layer is 2 μm and 5 μm. That is, it can be seen from this that when a thinner adhesive layer with a thickness of 5 μm or less is used, polyethylene terephthalate (PET) or a material with a lower elastic modulus (silicone rubber, etc.) must be used for the surface layer of the roller in contact with the resin film.

[0124] Thus, according to the results of the present embodiment and the comparative example, in the manufacturing step of the glass resin laminate, when the elastic modulus of the surface layer of the roller in contact with the resin film is set to P1 and the elastic modulus of the resin film is set to P2, by setting the ratio of the elastic modulus P1 to the elastic modulus P2 to satisfy 3×10 -3 By selecting the material of the surface layer of the roller in contact with the resin film so as to satisfy ≤P1 / P2≤1.0, the occurrence of bubble defects can be suppressed.

[0125] Furthermore, it was confirmed that, under the above conditions, the thinner the adhesive layer for bonding the glass film and the resin film together is, the better the effect is exerted, and the effect is particularly remarkable when the thickness of the adhesive layer is 5 μm or less.

[0126] It should be noted that, although the above description is made using a resin film with a polarizing plate as an example, the above conditions are effective in any method for manufacturing a glass-resin laminate having a step of bonding a glass film and a resin film together with an adhesive layer using two opposing rollers, and are not limited to a resin film with a polarizing plate. Examples other than the resin film with a polarizing plate include PET film, PEN film, and the like.

[0127] Although the preferred embodiments and the like have been described in detail above, the present invention is not limited to the above embodiments and the like, and various modifications and substitutions may be made to the above embodiments and the like without departing from the technical scope described in the claims.

[0128] This international application claims the benefit of priority based on Japanese Patent Application No. 2019-066162 filed on March 29, 2019, and the entire contents of Japanese Patent Application No. 2019-066162 are incorporated herein by reference.

[0129] [Explanation of Reference Numerals]

[0130] 1 Glass resin laminate

[0131] 10 Glass film

[0132] 20 Resin film

[0133] 21 Adhesive layer

[0134] 22 polarizing plate

[0135] 28 Adhesive layer

[0136] 29 Release film

[0137] 110, 120, 130, 140 rollers

[0138] 221 Polarizer

[0139] 222 No. 1 protective film

[0140] 223 Second protective film

Claims

1. A method for producing a glass resin laminate, characterized in that: have: The step of sandwiching a glass film and a resin film between a first roller for pressing the resin film and a second roller arranged opposite to the first roller and for pressing the glass film, and bonding the glass film and the resin film together via an adhesive layer, Wherein, the thickness of the adhesive layer is 0.1 μm to 5 μm, The elasticity of the adhesive layer is 1 GPa to 5 GPa, When the elastic modulus of the surface layer of the first roller is set to P1 and the elastic modulus of the resin film is set to P2, the ratio P1 / P2 of the elastic modulus P1 to the elastic modulus P2 satisfies 3×10 -3 ≤P1 / P2≤1.0, The surface layer of the first roller is formed of a material having an elastic modulus lower than that of iron. The surface layer is a region extending from the surface of the roller to 1 mm inward in the center direction. The surface layer of the first roller is formed of polyethylene terephthalate, polyethylene or polypropylene.

2. The method for producing a glass resin laminate according to claim 1, wherein: The thickness of the adhesive layer is 0.1 μm to 2 μm.

3. The method for producing a glass resin laminate according to claim 1 or 2, wherein: The resin film includes a polarizing plate, and the polarizing plate is disposed on the side of the adhesive layer opposite to the side bonded to the glass film.

4. The method for producing a glass resin laminate according to claim 3, wherein: The polarizing plate includes a polarizer and a protective film.

Citation Information

Patent Citations

  • Method for manufacturing film for optics

    JP2006309033A

  • Polarizer protective film, and polarizing plate using the same

    JP2006317560A

  • Base material for surface-protective film and surface-protective film

    JP2006328329A

  • Resin composition, optical film and polarizer protection film using the same

    JP2006328334A

  • Polarizer protecting film and polarizing plate using same

    JP2006337491A